Cassava mosaic diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Professor J. Michael Thresh, of the UK Natural Resources Institute, has responded to an article published in Spore entitled Malawi farmers unaware of effects of EACMD. Professor Thresh writes 'A recent feature in Spore 70 (p. 8) summarises an...